THE IMPLICATIONS OF GUARDED NEIGHBORHOOD ON HOUSING PRICES IN URBAN MALAYSIA - Tedong, Peter Aning; Zyed, Zafirah Al Sadat (Journal of Surveying, Construction and Property, 2021)
The research on gated communities has drawn considerable attention over the last three decades as researchers identify why certain social groups of people choose to live in a fortified neighborhood. Many scholars ranging from urban geographers, urban planning, anthropologist, urban economists, sociologists to urban politics have attempted to explore the reasons behind the proliferation of gated communities throughout the world. However, less research talked about the impacts of enclosure developments on housing prices, especially in developing countries like Malaysia. Therefore, this article will examine the various actors' perceptions of guarded neighborhoods' implications towards housing prices in urban Malaysia. This article found that various actors interviewed believe that guarded neighborhoods can improve the housing prices in Malaysia. This article contributes to the general understanding of Malaysia's guarded neighborhood and has multiple implications in terms of housing prices in enclosure developments.